2000
DOI: 10.1152/ajplung.2000.278.5.l914
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of the interleukin-10 gene into mice inhibited bleomycin-induced lung injury in vivo

Abstract: Interleukin (IL)-10 has been shown to reduce many inflammatory reactions. We investigated the in vivo effects of IL-10 on a bleomycin-induced lung injury model. Hemagglutinating virus of Japan (HVJ)-liposomes containing a human IL-10 expression vector (hIL10-HVJ) or a balanced salt solution as a control (Cont-HVJ) was intraperitoneally injected into mice on day -3. This was followed by intratracheal instillation of bleomycin (0.8 mg/kg) on day 0. Myeloperoxidase activity of bronchoalveolar lavage fluid and tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
86
3
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 43 publications
6
86
3
2
Order By: Relevance
“…This may be particularly relevant to the airway remodeling in asthma, the fibrosis in interstitial lung diseases such as silicosis, and the salivary gland scarring seen in Sjogren's syndrome. These studies do not, however, support the concept that IL-10 is anti-fibrotic, as has been proposed by other investigators (69). In circumstances where anti-fibrotic effects of IL-10 are seen, our data would suggest that the decrease in fibrosis is a result of the ability of IL-10 to diminish tissue inflammation and inflammation-induced injury and not direct effects of IL-10 on matrix deposition or structural cell proliferation.…”
Section: Discussioncontrasting
confidence: 99%
“…This may be particularly relevant to the airway remodeling in asthma, the fibrosis in interstitial lung diseases such as silicosis, and the salivary gland scarring seen in Sjogren's syndrome. These studies do not, however, support the concept that IL-10 is anti-fibrotic, as has been proposed by other investigators (69). In circumstances where anti-fibrotic effects of IL-10 are seen, our data would suggest that the decrease in fibrosis is a result of the ability of IL-10 to diminish tissue inflammation and inflammation-induced injury and not direct effects of IL-10 on matrix deposition or structural cell proliferation.…”
Section: Discussioncontrasting
confidence: 99%
“…The contribution of IL-10 to fibrosis is much less clear, although several recent studies suggest that it may play an important regulatory role. 7,[44][45][46] Using a model of carbon tetrachloride-induced liver injury, Thompson et al demonstrated an increased fibrotic response in IL-10 -deficient mice. 47 We, however, failed to observe a similar response in schistosome-infected mice, because fibrosis was only variably affected by the absence of IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…9 The role of IL-10 in fibrosis has been also reported in other organs such as lung, heart and pancreas fibrosis. [10][11][12] The underlying mechanism of antifibrotic effects of IL-10 remains unclear, but it has been suggested that IL-10 can suppress extracellular matrix synthesis and inhibit key inflammatory pathways such as NF-kB. [13][14][15] In the context of kidney, IL-10 has been reported to effectively suppress the progression of acute and chronic renal damage in vivo.…”
mentioning
confidence: 99%